PENGARUH DANA PIHAK KETIGA, BIAYA OPERASIONAL, BI RATE, DAN INFLASI PADA PENDAPATAN MARGIN MURABAHAH - Yuli Mustikawati; Muhammad Ali Fikri (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2021)
The purpose of this study is to determine the effect of third party funds, operational costs, BI rate and inflation on murabahah margins income of Islamic commercial banks in Indonesia. This research data uses secondary data in the form of quarterly financial reports of Islamic commercial banks in 2015-2019. The total population used was 14 Islamic commercial banks registered with the Financial Services Authority during the 2015–2019 period. Sampling using purposive sampling technique and data processing using the Eviews 9 application. Results: First, third party funds have a positive effect on murabahah margin income. Second, operating costs have a positive effect on murabahah margin income. Third, the BI rate has a negative effect on murabahah margin income. Fourth, inflation has a positive effect on murabaha margin income.